A COMPETENT APPROACH TO TEACHING RIDDLES IN PRIMARY EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article analyses about the  methods of teaching the riddle genre in elementary grades. In the process of analysis, the peculiarities of this genre  are also covered and its relationship with other sub-genres.